HUBUNGAN ANTARA PEMAHAMAN PENGGUNAAN APLIKASI ACCURATE TERHADAP HASIL BELAJAR SISWA - Rijal, Elsa Erlian Sinaga, (FKIP UMN ALWASHLIYAH, 2023)
This study aims to determine the relationship between the ability of accounting students and learning outcomes in using the Accurate application in class XI students of SMK Tunas Karya Batang on the 2021-2022 FY quiz. This development module uses the Accurate application to facilitate students in learning about accounting. Determination of the subject is done by interview and survey, which consists of 30 students for a trial using the Accurate application. The data collection technique was done by using a questionnaire. This questionnaire is used to assess the modules developed in terms of module completeness, material content and the physical appearance of the module. Data were analyzed descriptively quantitatively and qualitatively. The results of hypothesis testing show that the value of tcount is 4.073 while ttable is obtained for N = 30 at a significant level of 95% (α=0.05) and dk = n – 1 = 30 – 1 = 29 of 1.69. By comparing tcount with ttable, it is obtained that tcount > ttable is 4.073 > 1.69. Thus, it can be concluded that